Pharmacological treatments of fibromyalgia in adults; overview of phase IV clinical trials - Nasser M. Alorfi (Frontiers Media S.A., 2022)
Background: Fibromyalgia is a chronic neurological condition characterized by widespread pain. The effectiveness of current pharmacological treatments is limited. However, several medications have been approved for phase IV trials in order to evaluate them.Aim: To identify and provide details of drugs that have been tested in completed phase IV clinical trials for fibromyalgia management in adults, including the primary endpoints and treatment outcomes. This article was submitted to Neuropharmacology, a section of the journal Frontiers in Pharmacology.Method: Publicly available and relevant phase IV trials registered at ClinicalTrials.gov were analyzed. The uses of the trialed drugs for fibromyalgia were reviewed.Results: As of 8 August 2022, a total of 1,263 phase IV clinical trials were identified, of which 121 were related to fibromyalgia. From these, 10 clinical trials met the inclusion criteria for the current study. The drugs used in phase IV trials are milnacipran, duloxetine, pregabalin, a combination of tramadol and acetaminophen, and armodafinil. The effectiveness of the current pharmacological treatments is apparently limited.Conclusion: Due to its complexity and association with other functional pain syndromes, treatment options for fibromyalgia only are limited and they are designed to alleviate the symptoms rather than to alter the pathological pathway of the condition itself. Pain management specialists have numerous pharmacologic options available for the management of fibromyalgia.